畢氏定理 證明 2

\begin{equation}\because\triangle\mathrm{ABC}\sim\triangle\mathrm{AHB}\end{equation}

\begin{equation}\therefore\mathrm{b}:\mathrm{c}=\mathrm{c}:(\mathrm{b}+\mathrm{x})\end{equation}

\begin{equation}\Rightarrow\mathrm{b}^2+\mathrm{bx}=\mathrm{c}^2\cdots\cdots(\mathrm{1})\end{equation}

\begin{equation}\because\triangle\mathrm{ABC}\sim\triangle\mathrm{BHC}\end{equation}

\begin{equation}\therefore\mathrm{b}:\mathrm{a}=\mathrm{a}:\mathrm{x}\end{equation}

\begin{equation}\Rightarrow\mathrm{bx}=\mathrm{a}^2\cdots\cdots(\mathrm{2})\end{equation}

\begin{equation}將(\mathrm{2})代入(\mathrm{1})可以即可得到\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{b}^2=\mathrm{c}^2\end{equation}

Reference:

1. Elisha S. Loomis (1935): « The Pythagorean Proposition ». p. 42.

發佈留言